2020
DOI: 10.1101/2020.10.09.20209379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cardiac Arrhythmias in Patients with COVID-19: A Systematic review and Meta-analysis

Abstract: Background: Cardiac arrhythmia cannot be overlooked in patients with coronavirus disease 2019 (COVID-19) as it carries a great influence on the outcomes. Hence, this study aimed to build concrete evidence regarding the incidence of cardiac arrhythmia in patients with COVID-19. Methods: We performed a systematic search for trusted databases/search engines including PubMed, Scopus, Cochrane library and web of science. After screening, the relevant data were extracted and the incidences from the different inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 29 publications
0
3
0
1
Order By: Relevance
“…Two reviews rated moderate quality examined the incidence of arrhythmia developed during hospitalization with COVID-19. 29 , 42 The larger of these reported incidence of arrhythmias as 18.4% (95% CI 7.8–32.3%). 42 One moderate quality review of four studies (245 patients) estimated the incidence of acute cardiac failure with COVID-19 as 6.5% (2.2%–12.2%), considerable heterogeneity ( I 2 = 78%).…”
Section: Resultsmentioning
confidence: 93%
“…Two reviews rated moderate quality examined the incidence of arrhythmia developed during hospitalization with COVID-19. 29 , 42 The larger of these reported incidence of arrhythmias as 18.4% (95% CI 7.8–32.3%). 42 One moderate quality review of four studies (245 patients) estimated the incidence of acute cardiac failure with COVID-19 as 6.5% (2.2%–12.2%), considerable heterogeneity ( I 2 = 78%).…”
Section: Resultsmentioning
confidence: 93%
“…HCQ and CQ are traditional antimalarial and autoimmune disease drugs that have been shown to control the SARS-CoV-2 infection in vitro [ 93 ], although the cardiotoxicity of HCQ and CQ should not be neglected. Several systematic reviews included in our study showed an association between these drugs and an increase in serious ventricular arrhythmia [ 21 22 29 ]. Since these reviews have been published, several randomized controlled trials have been performed.…”
Section: Discussionmentioning
confidence: 92%
“…Incidence of arrythmias ranged from 1.8% to 26% in hospitalized COVID-19 patients [ 21 22 23 24 25 26 27 28 29 ], while an incidence of 33% to 48% was reported in severe disease [ 21 25 26 29 30 ]. Newly occurring arrhythmias in COVID-19 patients predicted severe disease and/or mortality [ 21 25 30 31 32 33 34 ].…”
Section: Resultsmentioning
confidence: 99%
“…El 56,6% de los pacientes hospitalizados con CO-VID-19 en nuestro estudio presentaron alteraciones electrocardiográficas; comparado con otros trabajos consultados, la proporción fue ligeramente superior [12][13][14] . Pese a ello, cuando se analizaron pacientes graves ingresados en unidades de cuidados intensivos los resultados de nuestro estudio fueron similares e incluso ligeramente inferiores 15,16 .…”
Section: Resultsunclassified